PENINGKATAN HASIL BELAJAR KELAS VI DALAM MENENTUKAN VOLUM BANGUN RUANG MELALUI PENGGUNAAN ALAT PERAGA KUBUS SATUAN - Widayanti, Eni (Jurnal Inovasi Pembelajaran di Sekolah, 2022)
Based on the learning outcomes of students during the pre-cycle at SD Negeri Kalibanteng Kidul 01 on Basic Competency, determining the volume of the average spatial structure of students' learning outcomes is still low, namely 64. This is a problem for teachers to improve learning outcomes in these Basic Competences. Efforts made through the use of unit cube teaching aids are expected to be able to improve learning outcomes in Basic Competence in determining the volume of geometric shapes. The formulation of the problem posed in this scientific paper reads "Is the use of unit cube teaching aids able to improve the learning outcomes of class VI students at SD Negeri Kalibanteng Kidul 01, West Semarang District, Semarang City in determining the volume of geometric shapes (blocks and cubes)? The purpose of this study was to improve the learning outcomes of class VIB students at SD Negeri Kalibanteng Kidul 01, West Semarang District, Semarang City in determining the volume of geometric shapes (beams and cubes) through the use of unit cube teaching aids. The benefits of this research for students are increased learning outcomes Basic Competence determines the volume of geometric shapes, for teachers it improves the quality of learning and for schools it can make a positive contribution to efforts to improve student learning outcomes. This research used classroom action research (CAR), carried out for two cycles, the data collection method of this research used observation and tests. The research subjects were students of class VI. the indicator of the success of this study is if the average class has obtained a Minimum Completeness Criteria score of 80. From the results of the study it was found that the learning outcomes of students in the Basic Competency determining the volume of geometric shapes (beams and cubes) reached an average of 6.8 in cycle I and 8.5 in cycle II. Based on these results, it is concluded that the use of unit cube teaching aids can improve student learning outcomes in these Basic Competences. From the results of observations it can also be seen that there is an increase in activity in learning.